Bishop professor Walenty Wójcik as a researcher of Synodal law - GÓRALSKI, WOJCIECH (Prawo Kanoniczne, 2018)
The achievements of professor Walenty Wójrcik (1914-1990), a long standing professor of the Catholic University of Lublin, in the field of Synodal law allow to assume that we deal with a considerable output, which is thematically diversified, original, creative and includes both issues and matters related to local and European synods, both historical and modern ones. His publications are characterized by references to a wide source base (the Author carried out a number of tedious preliminary research studies inter alia in archives in Rome), a thorough knowledge of literature (including foreign literature), a critical approach to analyzed issues, clear form and methodological purity. Therefore, it is not surprising that this output has always been highly recognized by reviewers in exams for promotion. As a prominent historian of Church law, he turned out to be an insightful and diligent researcher, who addressed less popular issues requiring euridition and hours of work – especially given the fact that research work was not the only matter around which the life of bishop, who was strongly committed to affairs of the diocese, focused on. Without a doubt, his passion for research played an important role in this matter